Ervilhaca peluda (Vicia villosa Roth) associada a fertilização nitrogenada visando a homogeneização da produtividade do milho das zonas de manejo - Gebert, Fábio Henrique (2018)
The different productivities in each management zone are usually linked to the intrinsic characteristics of the soil and landscape found in each field. Corn is an important crop of economic interest that presents a high productivity response to nitrogen fertilization and growing environment. On the other hand, legume cover crops such as hairy vetch can contribute with the minimization of the greasy effects of these factors and help to reach more homogenous productivities within the management zones through the improvement of cultivation environments and biological nitrogen fixation. In this way the work due to investigate the contribution in yield of maize delivered by the presence of hairy vetch associated with, or not, mineral nitrogen fertilization in different management zones. The research was carried out in two commercial areas located in the city of carazinho, southern Brazil with Typic Hapludox Soil. The management zones were delineated using one yield map from previous year, soil apparent electric conductivity from two depths (0-30 cm and 0-90 cm), terrain elevation and slope. The experimental design was a complete randomized block with three repetitions located within each MZ and the treatments consist of five N rates (0, 60, 120, 180, 240 kg ha-1) with and without hairy vetch (HV) in a tree MZ. No interactions were observed between the three factors for the variables for apparent nitrogen recovery, maize productivity and nitrogen reduction efficiency. However, all double interactions were significant (p>0.05). Nitrogen recovery was 23, 27 and 20% for the low, medium and high yielding areas, respectively for the first experiment and 29, 26 and 17% for the low, medium and high productivity zones in the second experiment. Thus, hairy vetch contributed to all management areas, but low and medium productivity environments were more favored by the presence of cover crop, probably explained by the presence of less favorable topographic elements for crop development and nitrogen recovery applied in coverage. The amount of apparent nitrogen fixed by hairy vetch culture was 64 kg N ha-1 for the first experiment and 54 kg N ha-1 for the second experiment. Moreover, since productivity differences were not found after the use of 120 kg N ha-1 for the first experiment and 180 kg N ha-1 for the second experiment.